POLA DESAIN MODEL-VIEW-VIEW MODEL UNTUK PENGEMBANGAN APLIKASI CALORIE COUNTER YANG EFISIEN - Fajar, Mohammad; Hijaya, Daniel Alexander; Hasniati (STMIK KHARISMA Makassar, 2025)
This study aims to design an efficient calorie counter application using Model-View-ViewModel (MVVM). The use of the Model-View-ViewModel design pattern is based on efforts to facilitate the process of reusing source code (Reusability). The design process uses flutter as an application framework. This research can be used as a reference regarding the Model-View-ViewModel, as well as providing new knowledge for researchers regarding the combination of the Model-View-ViewModel design pattern with the flutter framework on the android platform. Data collection in this study was carried out through literature studies and evaluation of the system design. The application was developed using the Dart programming language, while the evaluation of the implementation of MVVM design pattern is measured by using CK metrics. The evaluation shows that the MVVM calorie counter application can be run on Bluestacks Android Emulator successfully. The reusability degree of the application is better than the non-MVVM calorie counter apps, where the WMC parameter decreased by 4.5 points, and the DIT parameter by 0.3 points, while the CBO parameter decreased by 0.4 points, and the LCOM parameter by 31.2 points. The results indicate that the MVVM calorie counter application is easier to maintain.